Seaweed diversity in the North Atlantic Ocean. - Tittley, Ian (Universidade dos Açores, 2002)
Seaweed species-richness in the arctic and temperate North Atlantic Ocean (north of 39º N) is reviewed. Comparisons with other oceanic areas show, for example, the Indian Ocean to be richer in species but the northern North Atlantic Ocean to have a greater diversity of brown algal genera. Comparisons between North Atlantic regional floras show the north-east Atlantic to be richer in species than the north-west, and a gradient of species richness to occur from south to north along both coasts. The area comprising Ireland, southern England, Atlantic France and Spain may be considered a “hot-spot” of species richness. The mid-Atlantic Azores archipelago has been recently shown to be richer in species than sites on the American coast and in northern Europe. The conservation of seaweed biodiversity is briefly considered.